The challenges faced by integrating Islamic corporate governance in companies of Gulf countries with non-Islamic companies across border through merger and acquisition - Bindabel, Wardah; Patel, Ashok; Yekini, Kemi C. (Australasian Centre for Research and Development, 2017)
One method of achieving company expansion to address new markets and access cheaper funds is through international mergers and acquisitions (M&A). The companies in the Gulf zone following Islamic principles are keen to engage with non-Islamic companies, for example, European companies to access the benefits of globalization. However, for such takeover to succeed, congruence between the organization culture and the control system is necessary. The potentially diverse external legal and political environments can generate areas of concerns, which can only be addressed through harmonization of the corporate and financial governance of such organizations. There is a considerable body of literature on differences between Islamic and conventional corporate governance (CG), especially on financial models. However, not much research has been conducted on international M&A between companies following Islamic and the conventional CG. Such research is necessary, especially between different Islamic countries, to better the understand critical issues and let companies make more informed decisions. This study investigates the variation and extent of the Shariah CG code compliances among Islamic companies in three Gulf countries, namely Saudi Arabia, Kuwait, and the United Arab Emirates, and how it affect international crossborder M&A among the companies with the western ones. It was found that despite the strong economic and cultural ties between the Gulf countries states; there was diversity in the application of Islamic law within the selected countries and its effect on the international M&A. This paper can provide some insights view in controlling and organizing the M&A activities between Islamic and non-Islamic financial institutions, as the Islamic governance in practical terms, cannot be viewed as an identical homogenous practice across the Islamic domain. Cultural variations do exist.